Application of Problem-Based Learning (PBL) on Hydrocarbon Compound Lesson to Increase Student Learning Outcomes - Nur Gaib Karepesina; Julita B. Manuhutu (Universitas Pendidikan Mandalika, 2023)
This study aims to improve the learning outcomes of 11th grade Science 4 state senior high school (SMAN) 3 Ambon on the subject material of hydrocarbon compounds by using the Problem-Based Learning model. This research was conducted with 37 11th-grade Science 4 students as the research sample. The data was collected by tests, observation sheets, and worksheets. Data were analyzed descriptively by percentage and n-gain with categories. The results of the research showed that the student’s learning outcomes were achieved with different qualifications. There are 2 students (5.41%) who had very good qualifications, 27 students (72.97%) were in good qualifications, 5 students (13.51%) are in fair qualifications, and 3 students (8.11%) are in poor qualifications/failed. N-gain achievement of 28 (75.68%) students was in the high category and 9 (24. 32%) students were in the medium category. The results of the analysis of the average normalized gain score for all students are 0.77 which is in the high category. Therefore, the Problem-Based Learning (PBL) model can improve student learning outcomes.